To Study the Influence of HR Practices Viz. Compensation and Benefits, Flexible Work Practices on Job Satisfaction in Gen Z Employees. - Anjali Shahi, Santoshi Sen Gupta, Sapana Shahi (Journal of Informatics Education and Research, 2025)
Generation Z, the youngest generation who is very frequently entering the workforce keeping in mind the very positive perspective on their careers and workplace norms. Employers need to openly welcome this generation and should use their positive strength while providing them the meaningful work at the workplace. In this regard, the paper aims to examine the effects of two major HR practices i.e. compensation and benefits and flexible work practices on job satisfaction in gen Z employees. This paper came up with findings that compensation and benefits and flexible work practices positively influence job satisfaction in Gen Z employees. In addition this paper states that the compensation and benefits have strong positive influence on job satisfaction in gen Z employees whereas flexible work practices have weak positive influence on job satisfaction in Gen Z employees. Both these HR practices play a significant role in job satisfaction in Gen Z employees which ultimately also effects their work behaviour. The paper encompasses an amalgam of HR practices and policies especially for Generation Z to achieve organizational goals and also the means to attract, motivate, and retain them. The paper begins with a comprehensive explanation of theoretical framework in terms of HR policies and practices for Gen Z, guiding theoretical lenses and the conceptual framework, followed by the methods to test the hypothesis propositions and the implication of the finding of the theory and practice while concluding its limitations and scope for future research.